2003
DOI: 10.1176/appi.ajp.160.12.2099
|View full text |Cite
|
Sign up to set email alerts
|

The McLean-Harvard First-Episode Mania Study: Prediction of Recovery and First Recurrence

Abstract: Within 2-4 years of first lifetime hospitalization for mania, all but 2% of patients experienced syndromal recovery, but 28% remained symptomatic, only 43% achieved functional recovery, and 57% switched or had new illness episodes. Risks of new manic and depressive episodes were similar but were predicted by contrasting factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
366
6
11

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 418 publications
(408 citation statements)
references
References 40 publications
25
366
6
11
Order By: Relevance
“…However, a growing number of studies indicate that, for a significant number of patients, outcome is quite poor, with high rates of relapse, chronicity, lingering residual symptoms, subsyndromes, cognitive and functional impairment, psychosocial disability, and diminished well-being. [2][3][4][5] Suicide is estimated to be the cause of death in up to 15% of individuals with mood disorders. In addition to this serious health risk, systemic manifestations of other medical conditions commonly co-occur in patients with a mood disorder.…”
Section: Introductionmentioning
confidence: 99%
“…However, a growing number of studies indicate that, for a significant number of patients, outcome is quite poor, with high rates of relapse, chronicity, lingering residual symptoms, subsyndromes, cognitive and functional impairment, psychosocial disability, and diminished well-being. [2][3][4][5] Suicide is estimated to be the cause of death in up to 15% of individuals with mood disorders. In addition to this serious health risk, systemic manifestations of other medical conditions commonly co-occur in patients with a mood disorder.…”
Section: Introductionmentioning
confidence: 99%
“…32 A recent study from the Systematic Treatment Optimization Program for Early Mania Project (STOP-EM) recruited a cohort of patients with BD type I without psychosis (n=53). 31 Almost 90% achieved syndromic recovery and 53% had symptom recurrence during 1-year follow-up (Table 2). Functional outcomes were not reported.…”
Section: First Episode Of Mania (Stage Ii)mentioning
confidence: 97%
“…Psychotic features, low premorbid occupational status, and non-mixed initial mania were related to new manic episodes, while higher occupational achievement, initial mixed dysphoric states, and psychiatric or medical comorbidity were associated with new depressive episodes ( Table 3). 31 In a cohort of 87 patients with first-episode psychotic mania, Conus et al found 90% syndromic, 60% symptomatic, and 39% functional recovery at 12-month follow-up. 7 Patients without family history of affective disorders, without substance use, and older age were more likely to achieve functional recovery after 12 months.…”
Section: First Episode Of Mania (Stage Ii)mentioning
confidence: 98%
See 2 more Smart Citations